Hubungan Stres Akademik dengan Kualitas Tidur Terhadap Siswa Kelas XII - Rizka, Maulid Dhiva Yuanshanda; Priasmoro, Dian Pitaloka; Koesrini, Juliati (Jurnal Keperawatan Florence Nightingale, 2025)
Academic stress is a form of psychological pressure commonly experienced by high school students. This pressure can affect physiological balance, including sleep quality, which plays an important role in the recovery of bodily and cognitive functions. Students' concentration, mental health, and academic performance can be affected by poor sleep quality. The purpose of this study was to determine the correlation between academic stress and sleep quality in 12th grade students at SMAN 1 Sumberpucung, Malang Regency. This study used a quantitative research method with a cross-sectional correlational design. The study population consisted of 413 12th grade students at SMAN 1 Sumberpucung, Malang Regency. Samples were taken using proportionate stratified random sampling, totaling 203 grade XII students. Data collection was conducted using the ESSA (Educational Stress Scale for Adolescents) questionnaire to measure academic stress and the PSQI (Pittsburgh Sleep Quality Index) questionnaire to measure sleep quality.  The findings revealed that 124 students (61.08%) experienced high academic stress and 111 students (54.55%) experienced poor sleep quality. The findings showed that the majority of 12th grade students at SMAN 1 Sumberpucung in Malang Regency experienced high academic stress and poor sleep quality. A p-value ≤ 0.01 was obtained from the Spearman Rank statistical test, indicating a significant relationship between academic stress and sleep quality among 12th-grade students at SMAN 1 Sumberpucung in Malang Regency. Nursing practices are recommended to focus on stress management and healthy sleep education, routine screening, and collaboration with schools and parents to support students' mental health.